2021
DOI: 10.3390/clinpract11040110
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiological Characteristics of COVID-19 Patients with SARS-CoV-2 Re-Detected on PCR Test after Discharge from Isolation

Abstract: There have been multiple reports of patients with coronavirus disease (COVID-19) testing positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) after discharge; however, information on the characteristics of such cases is limited. In this case report, we aimed to identify clinical and epidemiological characteristics of patients who had a repeat positive polymerase chain reaction (PCR) test for SARS-CoV-2. We analyzed data of 22 COVID-19 patients who tested positive for SARS-CoV-2 on polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Furthermore, diagnostic tests involving hematological parameters, such as blood gas analysis and inflammatory biomarkers, can also support the test results. 11, 12 RT-PCR examination is generally used because of its high sensitivity. Previous studies showed that RT-PCR examination using oropharyngeal and nasal specimens had a sensitivity of up to 94.2% and 88.9%, respectively, with a specificity of up to 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, diagnostic tests involving hematological parameters, such as blood gas analysis and inflammatory biomarkers, can also support the test results. 11, 12 RT-PCR examination is generally used because of its high sensitivity. Previous studies showed that RT-PCR examination using oropharyngeal and nasal specimens had a sensitivity of up to 94.2% and 88.9%, respectively, with a specificity of up to 100%.…”
Section: Discussionmentioning
confidence: 99%